Sabbath and Sunday: The meaning of the day of rest in the ancient church – A hope for the future? - Vaida, Cristian (HTS teologiese studies, 2023)
The Sabbath is part of Jewish tradition. In Christianity it has taken on a new meaning. Both faiths saw it as a gift from God, a tool to affirm one’s spiritual creed and identity, and a way to maintain a distinct faith identity. The secularism of contemporary society has resulted in a misinterpretation of the purpose of Sunday rest and a disregard for the spiritual aspects that the Sunday celebration involves. A false perception of Sunday rest has emerged in modern times: It is not perceived as a divine gift that enables a spiritual ministry, which leads to resistance and opposition to the restless anxiety of the consumerist world and serves as an alternative to advertising’s demanding presence in this world. This rest, as a gift from God, has been one of the most fundamental defining features of man’s connection with God throughout history. Since Christian antiquity, there has been substantial debate over how to observe this tremendous gift of rest. Rest was valued as a gift in the Jewish culture in a specific way that included defining the identity of the chosen people. Later, in the Christian tradition, it was connected to the celebration of Christ’s Resurrection and the spiritual healing He provided to the world. There has been much debate on the continuity and discontinuity between the Jewish Sabbath and the Christian Sunday, as well as on how the transition from the Sabbath to the Sunday celebration came about. The two qualities of the Jewish Sabbath – a day of rest and a day of religious celebration – have been transferred to the Christian Sunday but in a radically different context.Contribution: By analysing early Christian literature, this study aims to investigate how the concept of Sabbath rest was taken up and reconstructed in Christianity in the celebration of Sunday, and how spiritual work was a constant in the life of Christian communities up until the 4th century, when Sunday rest was established by law. Contrary to Rordorf’s opinions, this article aims to show that Christians, despite being physically obligated to work on Sundays, tacitly observed this day as a day of resurrection, emphasising the spiritual work of the virtues as their vehicle towards their entrance into the rest in God, even before Sunday became socially established as a day of rest (Heb 4:1–11). This study intends to show that this unique vision of the Sunday rest of the early church can be an element of resistance and an alternative to the demanding stress and restless anxiety of modern society.